Assessment of Hydrocarbon Oil Spill Pollutants in Agricultural Land - R. Arivarasan; D. Sathishkumar; Rengasamy, M. (Asian Journal of Engineering and Applied Technology, 2018)
Hydrocarbon contamination is a very serious problem whether it comes from petroleum, pesticides or other toxic organic matters. Oil spill have number of effects on the environment when petroleum products are released into the environment, they interact with the soil, groundwater, and microorganisms. Studies have mainly focused on identifying and characterizing these hydrocarbon degrading microbes, as well as how they scope with the soil/water/hydrocarbon interface, and how to improve this capacity. The main aim of the present study was to evaluate the biodegradation potential of microbes which was isolated from the hydrocarbon contaminated soil such as bacillus species and pseudomonas species. Those isolated microbes were inoculated into the contaminated soil, after 20 days of degradation process the physicochemical properties such as pH, temperature, color, GC-MS were analyzed and also prominent microbe was identified from the isolated microbes. Comparative study also done between aerated and non-aerated condition from that, aeration process enhanced the degradation rate.